Cell cycles and endocycles in the model brown seaweed Ectocarpus siliculosus - Bothwell, John H (Landes Bioscience, 2010)
The recent announcement of the first genome sequence of a brown macroalga, the filamentous Ectocarpus,1 has been accompanied by a number of companion papers in New Phytologist. In a paper which contributes to this special issue, we classified the core cell cycle components of Ectocarpus, comparing them to the previously studied cell cycle components of diatoms. We then carried out fluorescence microscopy experiments to show that the Ectocarpus cell cycle could be deregulated during early development to give endopolyploid adults. We discuss here how our findings complement recent studies on endopolyploidy in plant and algal systems.